Postnatal Mental Health, Hand Washing Practices, and Infant Illness in Rural China - Jiang, Qi; Cohen, Nourya; Ohtori, Mika; Gao, Jie; Wang, Qingzhi; Zhang, Evelyn; Zhu, Sabrina; Johnstone, Hannah; Guo, Yian; Dill, Sarah-Eve; Zhou, Huan; Rozelle, Scott (Frontiers in Global Women's Health, 2021)
Background: Maternal mental health problems are a major burden to global public health and play an important role in infant wellbeing. While western countries have extensively studied the associations between maternal mental disorders, infant health, and hygiene practices, little is known in developing settings. This study investigates the correlations between postnatal mental health problems and infant illness as well as handwashing practices of mothers in rural western China. Methods: The research team followed a multi-stage random cluster sampling method to select a total of 720 mothers of infants aged 0-6 months from poverty counties in rural western China. Surveys questions about mental health were based on the Depression, Anxiety, and Stress Scale-21 (DASS-21), and questions about infant illness and handwashing practices followed evaluative surveys of prior studies. Adjusted ordinary least squares (OLS) regressions were run to examine how postnatal mental health problems (including depression, anxiety, and stress symptoms) are associated with infant illnesses and maternal handwashing practices. Results: We found significant associations between all three symptoms of postnatal mental health and whether the infant had shown symptoms of illness twice in the past two weeks; depression and anxiety symptoms are significantly associated with whether the infant had been taken to the doctor in the past two weeks. Additionally, depression symptoms had a significant negative association with all categories of handwashing practices, and symptoms of anxiety and stress were significantly associated with handwashing count and frequently washing hands after cleaning infant’s bottom. Conclusion: These results indicate that postnatal mental health problems are significantly associated with infant illness and suggest that postnatal mental health interventions may be effective in mitigating poor infant health outcomes.